Quantitative Constraint on the Contribution of Resolved Gamma-Ray Sources to the Sub-PeV Galactic Diffuse Gamma-Ray Flux Measured by the Tibet ASγ Experiment - S. Kato; M. Anzorena; D. Chen; K. Fujita; R. Garcia; J. Huang; G. Imaizumi; T. Kawashima; K. Kawata; A. Mizuno; M. Ohnishi; T. Sako; et al. (The Astrophysical Journal Letters)
Motivated by the difference between the fluxes of sub-PeV Galactic diffuse gamma-ray emission (GDE) measured by the Tibet AS γ experiment and the LHAASO collaboration, our study constrains the contribution to the GDE flux measured by Tibet AS γ from the sub-PeV gamma-ray sources in the first LHAASO catalog plus the Cygnus Cocoon. After removing the gamma-ray emission of the sources masked in the observation by Tibet AS γ , the contribution of the sources to the Tibet diffuse flux is found to be subdominant; in the sky region of 25° < l < 100° and ∣ b ∣ < 5°, it is less than 26.9% ± 9.9%, 34.8% ± 14.0%, and $13.5{ % }_{-7.7 % }^{+6.3 % }$ at 121 TeV, 220 TeV, and 534 TeV, respectively. In the sky region of 50° < l < 200° and ∣ b ∣ < 5°, the fraction is less than 24.1% ± 9.5%, 27.1% ± 11.1%, and $13.5{ % }_{-7.6 % }^{+6.2 % }$ . After subtracting the source contribution, the hadronic diffusive nature of the Tibet diffuse flux is the most natural interpretation although some contributions from very faint unresolved hadronic gamma-ray sources cannot be ruled out. Different source-masking schemes adopted by Tibet AS γ and LHAASO for their diffuse analyses result in different effective Galactic latitudinal ranges of the sky regions observed by the two experiments. Our study concludes that the effect of the different source-masking schemes leads to the observed difference between the Tibet diffuse flux measured in 25° < l < 100° and ∣ b ∣ < 5° and LHAASO diffuse flux in 15° < l < 125° and ∣ b ∣ < 5°.